COVID-19 and entrepreneurial processes in U.S. equity crowdfunding - Douglas J. Cumming; Robert S. Reardon (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
COVID-19 brought about a shift in entrepreneurial opportunities and in the United States. In this paper, we proxy entrepreneurial processes by examining housing prices in different regions of the United States. Housing prices capture the movement in people, tax dynamics, and behavioral preferences for equity ownership in different regions and over time, all of which were drastically impacted by COVID-19. We examine all U.S. equity crowdfunding offerings starting with the very first offerings in 2016 Q2 until 2021 Q1 based on data from the Securities and Exchange Commission. The data indicate that regional housing prices post-COVID-19 are a strong predictor of the number of equity crowdfunding campaigns and the amount of capital raised. The impact of housing price changes on crowdfunding is more pronounced among more prosperous regions. The housing price effect is robust to numerous controls and consideration of outliers.
Keywords: G21; G28; G51; 330; Equity Crowdfunding; COVID-19; Regional Entrepreneurship